Biossorção de cobre, manganês e cádmio por biomassas de Saprolegnia subterranea(Dissmann) R.L. Seym. e Pythium torulosumCoker & P. Patt. (Oomycetes) - de Souza, Jose Ivanildo; Schoenlein-Crusius, Iracema Helena; Amorin Pires-Zottarelli, Carmen Lidia; Schoenlein, Norberto Carlos (Soc Botanica Brasil, 2008)
Dried biomass of the zoosporic fungi Saprolegnia subterranea and Pythium torulosum was evaluated for copper, manganese and cadmium biosorption from aqueous solutions using the "q" (mg of adsorbed metal per g of biomass) and the "R%" (percent removal) indices. The highest q values were observed when the biomass was placed in contact with high metal concentrations, whereas the highest R% values were observed at low concentrations (p< 0.05). S. subterranea SPC 1244 biomass surpassed the others for copper biosorption (q = 7.48 mg/ g; R% = 49.03), P. torulosum SPC 1425 biomass was the best for manganese biosorption (q = 4.13 mg/g; R% = 26.71), and S. subterranea SPC 1431 biomass was the best for cadmium biosorption (q = 6.75 mg/g; R% = 42.26). This is the first report on copper, manganese and cadmium biosorption by the biomass of these zoosporic fungi, indicating the potential to remove ions from diluted solutions.
Copper, manganese and cadmium biosorption by Saprolegnia subterranea (Dissmann) R. L. Seym. and Pythium torulosum Coker & P. Patt. (Oomycetes) biomass
Keywords: biosorption; heavy metals; Oomycetes; pollution